Inexistencia del reglamento del sistema nacional de rehabilitación social y el acceso de las personas privadas de libertad, a los regímenes semiabierto y abierto, respectivamente - Sarabia Almagro, Martha Isabel (2015)
The thesis called "LACK OF REGULATION OF REHABILITATION NATIONAL SOCIAL SYSTEM AND THE ACCESS OF PERSONS DEPRIVED OF FREEDOM, regimes SEMI-OPEN and open, respectively," basically refers to the potential negative effects that would be doomed persons deprived freedom to access the semi open and open regimes related theme Arts. 694, 695, 696, 698,699,701 and 704, referred to in Comprehensive Organic Penal Code; in order to get to clarify the level of knowledge held by detainees concerning the treatment axes and activities specifically covering these axes necessarily have to get involved to enjoy the semi-open and open regimes respectively, benefits granted by law, within the framework of the progressive regime and New Management Model Prison. In order to obtain first-hand information, I proceeded to obtain information from detainees that in its majority had been sentenced to the new Integral <Organic Criminal Code; Likewise, I interviewed legal professionals with extensive experience in social rehabilitation; information was supplemented with comparative law in the countries of Chile, Peru and Venezuela, inferring that all these laws studied the hands in this matter are very similar and even more, Peruvian law has a close relationship with the Ecuadorian Legislation specifically at the time of sentencing that private persons of freedom, must be met to access the benefits of the law; in the case of Ecuador, the semi-open and open regimes respectively. In field research, all the information obtained, was coded and analyzed, the results allowed me to see the General, specific objectives and the subsequent testing of hypotheses raised; ie effectively "The lack of regulation of the National Social Rehabilitation for the implementation, application and enforcement of the rules contained in Book III of the Code Integral Criminal attentive to the rights of detainees that Law rightful access regimes benefit of semi - open and open, respectively "; consequently was imminent propose an alternative solution through a Art. unnumbered attesting to timely in the Regulation of the National System of Social Rehabilitation and refers to all detainees who are involved in formal education activities , they are guaranteed access and quickly, the aforementioned regimes. I am sure and convinced that this proposal as an alternative solution to the existing problems, to be welcomed by the National University of Loja and being socialized to the Ministry of Justice, Human Rights and Religious competent body to elaborate and approved by the Lord President of the Republic of Ecuador, Econ. Rafael Correa Delgado and its subsequent entry into force, the detainees, see education as the most suitable to receive the benefits of resource law, and therefore to get their ultimate freedom